A Systematic Review of BIM Adoption and Implementation Challenges in Design & Build Contracts: Insights and Implications for Nepal - Mishra, Suman Kumar; Ayob, Mohamad; Ibrahim, Nurazim (Journal of Advanced Academic Research, 2026)
The design & build (D&B) projects can be made efficient, cost-effective, and quality-assured through Building Information Modeling (BIM). Its adoption is limited in developing countries. The paper is a PRISMA-based systematic review of 21 empirical and conceptual studies on the topic published between 2000 and 2025. The review investigates obstacles to BIM adoption as far as Nepal is concerned. Each study was treated as a qualitative case and therefore, a thematic analysis was carried out. Codes were determined and sorted into major themes. There were five significant obstacles, namely technical, organizational, financial, contractual, and policy or cultural. All situations had common technical and organizational barriers. There were greater financial, contractual, and policy-related impediments in the developing countries. Low industry maturity, high cost, fragmented practices, unclear contracts, and less support for regulations are some of the reasons that limit BIM adoption in Nepal. The results demonstrate the necessity of national BIM standards, capacity building, financial incentives, contractual reforms, and increased awareness of the stakeholders. The presented research offers evidence-based information to help enhance the implementation of BIM and achieve better cost, time, and quality results in resource-limited situations.